In vitro seed germination of archidendron pauciflorum (jering) / Nur Syahirah Azhar - Azhar, Nur Syahirah (2016)
Archidendron pauciflorum is known in medical field to have high medicinal value. It is collected for medical purposes including for cancer cases. Despite that, there is an obstacle for its production due to the presence of seed dormancy. Therefore growing the seeds in vitro was done to break the seed dormancy by using a few concentrations of different phytohormones. Tissue culture is one alternative to increase crop production hence, a study was conducted to see which plant hormone could help to increase the seed’s growth rate. Indole-3-acetic acid (IAA) and 1-Naphthaleneacetic acid (NAA) were added into the culture media each with different concentrations (1 - 5 mg/L). Results were shown as quickly as four days of inoculation where the seeds inoculated in the media with IAA had grown their shoot and roots; grew the best with the concentration of 1 mg/L under dim light condition. However, results were obtained only with 1 mg/L and 2 mg/L NAA due to the condition of the seeds where the embryos were dead in the concentration of 3 mg/L, 4 mg/L and 5mg/L. This matter should not be a concern as IAA evidently could be used to increase the growth of A. pauciflorum seeds. The result was assumed to be able to aid the plant production of this species.